Socialization and Sports (Texas Journal of Multidisciplinary Studies, 2022)
In line with the sports movement, the value of sports as a factor in the socialization and education of the individual increases, since various interpersonal relationships arise and manifest themselves directly in the process of sports activity and in connection with it. The totality of these relations forms the basis of the formative influence of sport on a person, the assimilation of social experience in the field of sports, and through it, more general social experience.